Controlled synergistic strategy to fabricate 3D-skeletal hetero-nanosponges with high performance for flexible energy storage applications. Issue 40 (18th August 2017) - Tebyetekerwa, Mike; Wang, Xingping; Wu, Yongzhi; Yang, Shengyuan; Zhu, Meifang; Ramakrishna, Seeram
Abstract : 3D-skeletal nanoarchitectures with high but dissimilar electroactivity performances are easily fabricated by effective spacing of electrospraying and electrospinning nozzles. Abstract : The simple combination of electrospinning and electrospraying has previously been studied by some researchers to fabricate novel nanomaterials for energy applications in batteries and supercapacitors. However, the performance of the resultant materials (especially electrodes) is not sufficient despite the collaboration of these two boundless methods. Herein, we report the best approach towards effective synergistic control of the two techniques to improve the electrochemical performance of the resultant electrode materials. Interestingly, the reported modified technique yielded unusual 3D-skeletal architectures with dissimilar but remarkable capacitance values. The current methodology is an easy and inexpensive approach to realizing 3D high-performance electroactive materials.